2018
DOI: 10.1016/j.mmcr.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pulmonary mucormycosis and aspergillosis in a patient with decompensated hepatic cirrhosis

Abstract: Invasive pulmonary mucormycosis and aspergillosis are rare, life-threatening fungal infections. Most documented cases have been reported in non-cirrhotic patients with diabetes mellitus, neutropenia, or treatment with corticosteroids. The prevalence of each infection is low among patients with hepatic cirrhosis. We report the first likely case of combined invasive pulmonary mucormycosis and aspergillosis in a male with decompensated hepatic cirrhosis. This report also highlights the first non-diabetic case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In our experience, the number of cirrhotic patients admitted in ICU increases, in an order of 5–10% each year. Our findings concerning the incidence of aspergillosis colonisation are consistent with previously published data [12, 13, 23, 24]. Indeed, the rate of fungal colonisation can reach 25% in critically ill cirrhotic patients, with Aspergillosis up to 3% [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our experience, the number of cirrhotic patients admitted in ICU increases, in an order of 5–10% each year. Our findings concerning the incidence of aspergillosis colonisation are consistent with previously published data [12, 13, 23, 24]. Indeed, the rate of fungal colonisation can reach 25% in critically ill cirrhotic patients, with Aspergillosis up to 3% [25].…”
Section: Discussionsupporting
confidence: 92%
“…Increasing numbers of fungal infections are also being observed [6, 7]. Among these pathogens, Aspergillus species, especially in respiratory samples, have emerged as an important cause of life-threatening infections in cirrhotic patients [813]. In immunocompromised patients, neutropenia and/or undergoing hematopoietic stem cell or solid organ transplantation, invasive pulmonary aspergillosis (IPA) is a major cause of morbidity and mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes stands as the strongest risk factor with a previous review of 929 patients found that 36% of the patients were diabetic [1] . Other rare association is liver cirrhosis as we found only 24 previous cases in literature [2] .…”
Section: Discussionmentioning
confidence: 62%
“…Diabetes mellitus stands as the strongest risk factor giving that 36% of patients with invasive mucormycosis were diabetic in a previous review of 929 cases [1] . Association with liver cirrhosis is rare and previous literature reviews revealed only few cases [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Zebra ish larvae at 4dpf show distinct characteristics of swimming pattern with respective to light conditions (Persichino et al, 2018). Here, zebra ish with the aim of developing a liver toxicity model to replace higher vertebrates was investigated.…”
Section: The Effect Of Ism On Alcohol-induced Liver Damage Analysismentioning
confidence: 99%